Solution for consolidation and retrofitting a historical steel bridge - Dorin Radu; Radu Băncilă; Dorel Bolduș; Simon Sedmak; Mihajlo Aranđelović (Elsevier - Procedia Structural Integrity, 2022)
Sustainable development is a fundamental goal of the European Union and seeks to meet the needs of the present, without compromising the future. The rehabilitation of historic steel constructions and old steel bridges in service, is part of the maintenance and conservation of existing heritage, thus considering a sustainable development concept, while constituting an act of culture. In present time, in Romania there are a relatively small number of steel bridges older than 100 years, especially in Transylvania region; they can be considered "witnesses of the past". Two important aspects are highlighted: consolidation costs are lower than for a new structure and the retrofitted bridge can receive a new, modern functional role that fits functionally into the landscape. The paper is presenting a study case for an existing steel bridge build in the beginning of twentieth century (around year 1925). There are presented solution for consolidation of the bridge and retrofitting, taken into account fatigue design and structural integrity assessment. Critical flaws values were determined for each case type using the failure assessment diagrams. These values are used as limit values for fatigue analysis based on fracture mechanics principles, to determine the number of cycles for a crack to extend from initial to critical dimension, i.e. failure. For the assessment was used the code cyclic loading as a block independent iterative solver – applying the specified stress ranges sequentially line by line, repeating the entire cyclic loading - entire group of cycles for a number of blocks (one block representing all the applied cycles of stress ranges).
Keywords: Structural integrity; Historical steel bridges